SÍNTESE DE ANÁLOGOS DE PEPTÍDEOS INCORPORADOS A MATERIAIS NANOPARTICULADOS DE CARBONO FUNCIONALIZADOS VIA REAÇÃO MULTICOMPONENTES - RHODEN, Cristiano Rodrigo Bohn (2018)
Every material has a potential for a determined purpose according to its intrinsic properties. However, these properties manifest as we already known them in a zone of limited size. When the size of this material is smaller than this zone, its properties turns differentiated. Thus, nanoscience and anotechnology (10-9) carry us into a realm of new possibilities. Considering the potential of carbon nanotubes in nanomedicine, it becomes necessary to increase the understanding of their behavior in applications such as drug or gene delivery, or specific treatment of cancer phototherapy for instance. However, controversial results, regarding the distribution, clearance, and toxicity were reported when the carbon nanotubes with different surface properties, and different concentrations, purity, and agglomeration state were studied. In order to contribute to their understanding, in vivo studies sought to acquire more knowledge about possible passageways and agglomeration that may provide greater subsidies regarding toxicity and real possibilities of their application as effective carriers of drugs. Recently has been reported that GO could be used as a strong oxidant to effectively oxidize Fe2+ in Fe3O4 nanoparticles that are deposited simultaneously on the surface of GO. Nanoparticles of graphene oxide (GO.Fe3O4) present magnetic and electrochemical behavior useful for potential energy storage applications, catalytic, biomedical applications, as well as for oxidation of metallic or non-metallic ions. Materials with antimicrobial and metallic absorption have been the object of research for biotechnological application in the development of materials with high efficiency and low toxicity. Multicomponent reactions (MCRs), established themselves as an important tool in organic synthesis studies, in the total synthesis of molecules either with defined activity or in combinatorial chemistry, providing high structural and functional diversity of molecules, for screening for the search of potentially active compounds. A variant of MCRs, the Ugi 4 component reaction (Ugi-4CR), have been successfully explored, and remain as a main study object in different research groups. In this framework, four chemical functionalities: an amine, a carbonyl group, an isocyanide and a carboxylic acid reacted simultaneously providing an peptide derivative, in good yields and furnishing only water as a byproduct. In this work, an easy and fast methodology to obtain the magnetic graphene oxide (GO.Fe3O4) was develop without the need of hydrothermal methods and using smaller amounts of FeCl2. Analyzes confirmed the lower amount of ferrite incorporated with maintenance of the magnetic activity of the material. Thus, allowing the application in the removal of contaminants through adsorption assays. The synthesis of carbon nanomaterials peptide derivatives was carried out employing Ugi-4CR in systems containing ferrite decorated graphene oxide and previously carboxylate carbon nanotubes (CNTs). Despite of established methods, the peptide or derivative is not linked into the nanostructures, but "grow" from them, allowing a greater structural diversity according to the substituent of the other functionalities involved in the reaction.